If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + 7) = -42 Reorder the terms: 5(7 + c) = -42 (7 * 5 + c * 5) = -42 (35 + 5c) = -42 Solving 35 + 5c = -42 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 5c = -42 + -35 Combine like terms: 35 + -35 = 0 0 + 5c = -42 + -35 5c = -42 + -35 Combine like terms: -42 + -35 = -77 5c = -77 Divide each side by '5'. c = -15.4 Simplifying c = -15.4
| 34+13+6a=100 | | 3(x+4)-6=-12 | | (x+20)+(x+10)+y+(y-40)=180 | | 2z+9.76-7z=-5.15 | | 12A+2+A-1= | | -2(t-1)+4t=6t-3 | | 16+346a=34 | | 7x^2+13x+1=3 | | 5x^3-9x^2-2x=0 | | -3(2s-6)-18=-3(9s+4)-3 | | -24=-8-6k+2k | | 95+-0.5y=180 | | 2x-5x+6.3= | | x^2-8x+16=22 | | -x+5x=-20 | | .4(c-8)+3=4 | | (8a^3-11)+(-5a-2)= | | 85+(-98)+21= | | 3i+-9-7i+21=6i+-16+-24 | | -10x-2x+3x= | | 2x-5(-3x+7)=-1 | | -20=-3x+8x | | 7r-9=-86 | | 4c+7-3c+8= | | -19=1-7p+8 | | 7r-2+5r=6r+6-4r | | 0.25+0.10(x-3)=1.1 | | 6y+3=4y-13 | | -4(23)= | | x+x+100=110 | | 100=8+9a | | 3(-6x+7)=-1 |